Survival in men diagnosed with prostate cancer in Poland in the years 2000 - 2014 compared to European Countries based on Concord-3 - Aleksandra Gliniewicz; Dorota Dudek-Godeau; Magdalena Bielska-Lasota (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Wealthy countries have observed in recent decades a fast-growing number of prostate patients, who require treatment and long-term cancer care. This trend seems to be connected with some demographic changes such as aging societies, better access to diagnostic methods with high sensitivity as well as large-scale secondary prevention (prostate cancer screening at early stage before clinical manifestation). Secondary prevention is becoming more accessible and widely applied. The expected effect of prevention is to improve overall survival while the mortality trend is decreasing. The prevention success requires highly effective healthcare system that must manage additional burden which is a consequence of the need to provide optimal treatment and healthcare in a big group of cancer patients diagnosed in effective prevention programms. According to the National Cancer Registry (NCR) the number of incidence from year 1980 - 1731 cases rose in year 2013 to 12 162 cases. Apart from incidence and mortality rates, the 5-year survival is a significant factor for the assessment of a population healthcare and healthcare system efficiency. The prognosis related to prostate incidence is 22 344 men in year 2025 in comparison to 12 162 in year 2013 - that would be a double rise in incidence. CONCORD-2 results (years 1995-2009) showed, among the others, that cancer curability for some cancers, including prostate cancer improved. In year 2018 the results of CONCORD-3 were published (years 2000-2014) showing a rising trend in improvement in prostate cancer curability in Poland Objective. The objective was to analyse the 5-year survival in prostate cancer patients in Poland, and in each of 16 voivodships, with the focus on changes in years 2000 - 2014 in comparison to European trends. Material and Methods. The analysis was based on the 5-year net survival (estimated in CONCORD-3) in prostate cancer patients diagnosed in Poland (NCR national data) and in all Polish voivodships. The 5-year survival of prostate cancer patients and its changes in years 2000 - 2014 compared between 16 voivodships, Poland in total and 28 European countries. Results. In Poland in years 2010 - 2014 the 5-year survival in prostate cancer patients was 78.1%, and compared to years 2000 - 2004 rose by 9.3 percentage points. Despite a systematic improvement in survival the differences between individual voivodships in Poland remained. In 6 voivodships the survival was higher than average for Poland and ranged from 80 to 82%. The lowest survival was in Opolskie voivodship - 72.3%. On a European scale, the curability of prostate cancer at that time was over 90% (9 countries), while Poland was among 5 countries whose total survival rate was less than 80% (from 72.3% - Opolskie voivodship to 83.6% -- Pomeranian voivodship). Conclusions. The 5-year survival in prostate cancer patients in years 2010 - 2014 in Poland was significantly lower in comparison to Western Europe countries, and favourable trends on a regional level in Poland were too slow to overcome high differentiation in Europe. It is expected that changing the structure and organisation of cancer care in Poland into a modern National Oncology Network Comprehensive Cancer Care Network, together with the use of the experiences from European projects, including iPAAC and better financing will contribute to improvement in prostate cancer treatment in Poland.